EFFECT OF DEPRESSION ON SLEEP QUALITY AND PAIN AMONG PATIENTS WITH ARTHRITIS DISEASE - Dr. Nighat Shaheen; Dr. Saima arzeen; Sidra Batool (Journal of Peace, Development and Communication, 2023)
The major aim of the present study was to examine the effect of depression on sleep quality and pain among patients with arthritis. The sample included (N=30) arthritis female patients recruited from outpatients of three main hospitals of Peshawar using Convenient Sampling Technique. Age range of the sample was between 45 to 65 years (M=54.51 ± 5.24). The inclusion criteria consisted of patients having diagnosed with hip and/or knee arthritis since one year on the basis of X-rays reports and currently were under treatment. The control group consisted of (N=26) female outpatients in the same age range who visited the OPD of the same hospitals for their less severe diseases. The Siddiqui Shah Depression Scale (Siddiqui & Shah, 1997) was used to measure depression, the Pittsburgh Sleep Quality Index (Buysse, Reynolds, Monk, Berman, & Kupfer, 1989) was used to assess quality of sleep and the Visual Analogue Scale (Gracely, McGrath, Dubner, 1978) was used to obtain data on the severity of pain in participants. Results showed that participants having higher baseline depression obtained significantly higher mean scores on the SSDS, the PSQI, and the VAS scales compared to the control group. The results support all hypotheses of the study. The findings have critical implications in clinical setting by suggesting an utmost need of treatment of the depression in arthritis patients in order to overcome their problem of sleep and reducing intensity of pain.